Liquidity management in Nigeria - Ariyo, Ademola (Lagos : West African Book Publishers, 2005)
Explores the liquidity situation in Nigeria and makes suggestions and recommendations towards evolving an inclusive and more purposeful liquidity management framework for the country.
"Magnum management series 1"--Jkt.
Includes bibliographical references (p. 181-187) and index.
oif 18/09/15
Loan
Keywords: Bank liquidity; Liquidity (Economics); Banks and banking